2022
DOI: 10.3389/fonc.2022.847745
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PCGEM1 in Human Cancers: Functions, Mechanisms and Promising Clinical Utility

Abstract: As novel members of the noncoding RNA family, long noncoding RNAs (lncRNAs) have been widely reported to function as powerful regulators in gene expression processes, including chromosome remodeling, transcription interference and posttranscriptional modification. With the rapid development of metagenomic sequencing, numerous studies have indicated that the dysregulation of lncRNAs is closely associated with diverse human diseases, especially cancers. Prostate Gene Expression Marker 1 (PCGEM1), a recently iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…LncRNA PCGEM1 was initially discovered to be overexpressed in prostate cancer and to promote tumor growth. It has since been found to have a similar effect in other cancers 122,123 . Han et al.…”
Section: Lncrna Participates In the Generation Of Anti‐cancer Drug Re...mentioning
confidence: 82%
See 2 more Smart Citations
“…LncRNA PCGEM1 was initially discovered to be overexpressed in prostate cancer and to promote tumor growth. It has since been found to have a similar effect in other cancers 122,123 . Han et al.…”
Section: Lncrna Participates In the Generation Of Anti‐cancer Drug Re...mentioning
confidence: 82%
“…It has since been found to have a similar effect in other cancers. 122,123 Han et al silenced PCGEM1 in LNCaP prostate cells and treated them with baicalein. They found that reducing PCGEM1 expression enhanced the inhibitory effect of baicalein on tumor cell proliferation and colony formation, induced apoptosis and autophagy and increased the sensitivity of LNCaP cells to baicalein.…”
Section: Baicaleinmentioning
confidence: 99%
See 1 more Smart Citation
“…FBXW11 maintained stem-cell-like characters and enhanced liver metastasis via governing SIRT1 transcription in colorectal cancer ( 38 ). LncRNA PCGEM1 has been found to participate in the initiation and development of a variety of cancers via regulating several signaling pathways ( 39 ). LncRNA PCGEM1 expression was remarkably increased in cervical cancer specimens, which was associated with FIGO stage, lymph node metastasis, poor survival and distant metastasis in cervical cancer patients ( 40 ).…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%
“…However, contribution of many other lncRNAs to this process has not been evaluated yet. HOTTIP, ANRIL, PANDAR, PCGEM1 and HOTAIR are among lncRNAs with established roles in the pathogenesis of human cancers, particularly those originated from endocrine organs [7][8][9] . The current study aims at assessment of expression of these lncRNAs in pituitary adenomas in comparison with the adjacent non-cancerous pituitary tissues.…”
Section: Introductionmentioning
confidence: 99%